Characterization of Protein Profiles and Their Role in Malting Quality of Commercial Barley Genotypes (Hordeum vulgare) - Zubillaga, María Fany (2025)
Fil: Zubillaga, María Fany. Universidad Nacional de Rio Negro (UNRN), Av. Don Bosco s/n, Viedma, Rio Negro, Argentina. Centro de Investigaciones y Transferencia de Rio Negro (CIT Rio Negro, CONICET- UNRN) Viedma, Rio Negro, Argentina